PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN IT CENTER DI DINAS BINA MARGA KABUPATEN KOTABARU - Sifa Fauziah (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
The purpose of the study is to know the application of good governance principle in managing the IT Center at Bina Marga Department Kotabaru regency. The researcher used descriptive qualitative research as the method of the study. From the result of the research, the researcher found that the application of Good Governance principle in managing IT Center at Bina Marga Department Kotabaru Regency was measured as well by using 9 principles, such as participation indicator, law indicator, transparency indicator, responsive indicator, consensus indicator, equilavment indicator, effectivity and efficiency indicator, accountability indicator, and visibility indicator. Lack of internet network and the minimum socialization occurred to be the obstacle factors in delivering the information. For the supporting factors, the researcher found human resource and information data became the supporting factors in managing IT center well.